1997
DOI: 10.1002/elan.1140091015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace vanadium in various waters by differential pulse adsorptive stripping voltammetry

Abstract: A sensitive voltammetric method is developed for the determination of trace amounts of vanadium in various water samples. The method is based on the preconcentration of the Vv-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) complex at a potential of -0.5 V (vs. Ag/ AgCI). The adsorbed complex is then reduced, producing a response with a peak potential of -0.8 V. The catalytic action of bromate ions on the reduction of the VV-5-Br-PADAP complex has also been investigated. The high catalytic currents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…The composition of the V(V)-ARS complex was determined by the mole ratio method to be 1 : 2. It was found that Pc 1 decreased with increasing the V(V) concentration and disappeared nearly when the concentration of V(V) was higher than half that of ARS, and Pc 2 did not be affected by the addition of bromate, in contrast to the previous observations [2,5,9,10,11,13,14] where the response signal for the V(V) complexes was enhanced catalytically in the presence of bromate. Moreover, the peak potential (E p ) of Pc 2 shifted toward more negative values with increasing scan rate (u).…”
Section: Methodscontrasting
confidence: 66%
See 1 more Smart Citation
“…The composition of the V(V)-ARS complex was determined by the mole ratio method to be 1 : 2. It was found that Pc 1 decreased with increasing the V(V) concentration and disappeared nearly when the concentration of V(V) was higher than half that of ARS, and Pc 2 did not be affected by the addition of bromate, in contrast to the previous observations [2,5,9,10,11,13,14] where the response signal for the V(V) complexes was enhanced catalytically in the presence of bromate. Moreover, the peak potential (E p ) of Pc 2 shifted toward more negative values with increasing scan rate (u).…”
Section: Methodscontrasting
confidence: 66%
“…Different ligands, such as catechol [1 -2], 5-Br-PADAP [3 -5], solochrome violet RS [6], 2-(2-thiazolylaloz)-p-cresol [7], pyrogallol [8], cupferron [9 -10], 2,3-dihydroxynaphthalene [11] and chloranilic acid [12 -13], have been used for the adsorptive voltammetric determination of vanadium. Several of these procedures involve a catalytic enhancement of the response in the presence of bromate [2,5,9,10,11,13]. Although the sensitivities of these methods at a hanging mercury drop electrode are fairly high, the mercury is becoming rather controversial material.…”
Section: Introductionmentioning
confidence: 99%
“…Since one of the routes of incorporation of V into the human body is water, [6][7][8] its determination in this type of sample is very important. The concentration of V in natural water is very low, [9][10][11] of the order of a few mg L 21 , hence powerful techniques are required and only a few of them show sufficient sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore determination of V (V) is receiving increasing attention in pollution studies. Since one of the routes of incorporation of V into the human body is drinking water (Hirayama et al, 1992;Rao et al, 1997;Sabbioni et al, 1996), its determination in these types of samples becomes very important. Since the concentration of V(V) in drinking water is very low (Greenbreg et al, 1975;Ahmed and Banerjee, 1995;Bermejo-Barrera et al, 1990), in the order of a few micrograms per liter, powerful techniques are required and only a few of them show sufficient sensitivity.…”
Section: Introductionmentioning
confidence: 99%